Fermented milk supplemented with pequi oil microcapsules: effects on physicochemical properties, stability, in vitro digestion, and bioaccessibility - SILVA, Luana Carvalho da; MAGALHÃES, Hilton César Rodrigues; FREIRE, Gabrielle Albuquerque; ALEXANDRE, Joana de Barros; CASTELO, Rachel Menezes; MUNIZ, Celli Rodrigues; FURTADO, Roselayne Ferro; ALVES, Carlucio Roberto (Food Science and Technology, 2023)
Pequi oil presents high levels of unsaturated fatty acids and beta-carotene and has been used for nutraceutical purposes. Microcapsules can improve the protection of bioactive compounds in pequi oil and mask the inherent smell and taste for food applications. However, the stability of the microencapsulated oil and its influence on the product characteristics need to be investigated. This work evaluated the impact of pequi oil microcapsules on the physicochemical characteristics of fermented milk and other aspects of stability, digestion, and bioaccessibility via the analysis of beta-carotene present in the oil. During 28 days of storage, the pH values decreased from 4.5 to 4.32 for all fermented milk. Syneresis values decreased (<50%) due to water retention caused by the biopolymers on the microcapsules. Microencapsulation promoted an improvement in oil stability and a gradual release for 120 min, which allowed a better condition for beta-carotene quantification in the micellar phase and resulted in better bioaccessibility. Thus, the microcapsules positively influenced the physicochemical properties of the fermented milk and improved oil bioaccessibility aspects.